2019
DOI: 10.5433/2236-6407.2019v10n3p43
|View full text |Cite
|
Sign up to set email alerts
|

Bem-estar subjetivo e resiliência em pessoas com Diabetes Mellitus

Abstract: Este artigo objetivou mensurar os níveis de Bem-Estar Subjetivo (BES) e de resiliência em diabéticos, além de verificar a correlação entre a resiliência e os fatores que compõem o bem-estar subjetivo. Foram aplicadas as escalas de BES e de resiliência em 104 diabéticos (média de idade= 56,16; DP= 13,01), residentes na cidade de João Pessoa- PB. Os resultados evidenciaram que 65,4% dos participantes apresentaram altos níveis de BES. Quanto à resiliência, constatou-se que a maioria possui entre moderada (63,5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
3
0
3
Order By: Relevance
“…The research results point out that most participants were female (85.5%) and married or in a stable relationship (53.6%), similar to a cross-sectional study conducted in João Pessoa-PB, that correlated the well-being and resilience in people with diabetes mellitus (82.7% female; 56.7% married) (9) . In the present research, men (p=0.033), people with higher income (p=0.003) and higher education level (p=0.001) had a higher resilience score, corroborating a study conducted in Israel during the pandemic, which showed worst indicators of psychological distress in women and the unemployed (1) .…”
Section: Discussionsupporting
confidence: 75%
“…The research results point out that most participants were female (85.5%) and married or in a stable relationship (53.6%), similar to a cross-sectional study conducted in João Pessoa-PB, that correlated the well-being and resilience in people with diabetes mellitus (82.7% female; 56.7% married) (9) . In the present research, men (p=0.033), people with higher income (p=0.003) and higher education level (p=0.001) had a higher resilience score, corroborating a study conducted in Israel during the pandemic, which showed worst indicators of psychological distress in women and the unemployed (1) .…”
Section: Discussionsupporting
confidence: 75%
“…Os resultados da pesquisa apontaram que a maioria dos participantes era do sexo feminino (85,5%) e pessoas casadas ou em união estável (53,6%), dados semelhantes a um estudo transversal realizado em João Pessoa-PB, que correlacionou o bem-estar e a resiliência em pessoas com diabetes mellitus (82,7% do sexo feminino;56,7% de casados) (9) . Na presente pesquisa, os homens (p=0,033), pessoas com maior renda (p=0,003) e maior escolaridade (p=0,001) apresentaram um escore mais alto de resiliência, corroborando com estudo realizado em Israel durante a pandemia, o qual evidenciou piores indicadores de sofrimento psíquico em mulheres e desempregados (1) .…”
Section: Discussionunclassified
“…However, in the historical and theoretical context of diabetes, it is observed that in the first half of the 20th century, diabetes mellitus manifested in children and adolescents in various ways [52]. A significant portion of patients presented with acute symptoms such as polyuria, polydipsia, dehydration, and ketosis, with rapid deterioration of clinical status, requiring insulin administration to reverse the condition [52]. However, cases were also observed where the disease presented more insidiously and often without ketosis association [53].…”
Section: Diabetesmentioning
confidence: 99%